Advances in Clinical and Basic Science of Coagulation: Illustrated abstracts of the 9th Chapel Hill Symposium on Hemostasis. Issue 3 (12th April 2018) - Bergmeier, Wolfgang; Antoniak, Silvio; Conway, Edward M.; Denis, Cécile V.; George, Lindsey A.; Isermann, Berend; Key, Nigel S.; Krishnaswamy, Sriram; Lam, Wilbur A.; Lillicrap, David; Liu, Jian; Looney, Mark R.; et al.
Abstract: This 9th Symposium on Hemostasis is an international scientific meeting held biannually in Chapel Hill, North Carolina. The meeting is in large measure the result of the close friendship between the late Dr. Harold R. Roberts of UNC Chapel Hill and Dr. Ulla Hedner of Novo Nordisk. When Novo Nordisk was developing the hemophilia therapy that would become NovoSeven, they sponsored a series of meetings to understand the basic biology and clinical applications of factor VIIa. The first meeting in Chapel Hill was held April 4‐6, 2002 with Dr. Roberts as the organizer. Over the years, the conference emphasis has expanded from discussions of factor VIIa and tissue factor to additional topics in hemostasis and thrombosis. This year's meeting includes presentations by internationally renowned speakers that discuss the state‐of‐the‐art on an array of important topics, including von Willebrand factor, engineering advances, coagulation and disease, tissue factor biology, therapeutic advances, and basic clotting factor biology. Included in this review article are illustrated abstracts provided by our speakers, which highlight the main conclusions of each invited talk. This will be the first meeting without Dr. Roberts in attendance, yet his commitment to excellent science and his focus on turning science to patient care are pervasively reflected in the presentations by our speakers.